Effect of processing techniques on the performance of Epoxy/MWCNT nanocomposites. Issue 6 (31st May 2012) - Hosur, Mahesh; Barua, Rajib; Zainuddin, Shaik; Kumar, Ashok; Trovillion, Jonathan; Jeelani, Shaik
Abstract The aim of this study is to investigate the optimum technique to disperse Multi‐Walled Carbon Nanotubes (MWCNTs) in SC‐1 epoxy uniformly and to evaluate the effect of processing technique on the performance of SC‐1 epoxy. To achieve better dispersion, MWCNT was mixed with SC‐1 resin directly or premixed with a solvent and then mixed with SC‐1 resin after evaporating the solvent using sonication, thinky mixing and three‐roll mill methods either in isolation or combination. Flexural tests were performed to evaluate mechanical performances and results exhibit up to 27.13, 13.51, and 21.99% improvement on flexural strength, flexural modulus, and maximum strain, respectively, over neat epoxy with only 0.2 wt % loading. Dynamic mechanical analysis (DMA), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) indicated improvement in storage modulus, Tg, inflection temperature, and residue content, respectively over neat SC‐1 epoxy. Thermal and mechanical properties at higher loading conditions were seen to either reduce or not significantly improve. This was attributed to high viscosity of nanocomposites as determined by rheological analysis which prevents good dispersion of MWNCTs into epoxy system at 0.4 wt % loading. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013